2018
DOI: 10.4103/sni.sni_88_18
|View full text |Cite
|
Sign up to set email alerts
|

The role of inflammation and potential use of sex steroids in intracranial aneurysms and subarachnoid hemorrhage

Abstract: Background:Aneurysmal subarachnoid hemorrhage (aSAH) continues to be a devastating neurological condition with a high risk of associated morbidity and mortality. Inflammation has been shown to increase the risk of complications associated with aSAH such as vasospasm and brain injury in animal models and humans. The goal of this review is to discuss the inflammatory mechanisms of aneurysm formation, rupture and vasospasm and explore the role of sex hormones in the inflammatory response to aSAH.Methods:A literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 153 publications
(178 reference statements)
0
3
0
Order By: Relevance
“…Evidence from numerous studies shows that immune cells participate in initiation of IA by triggering production of molecules that initiate inflammation, as well as factors that induce pathological remodeling of vasculature. [30][31][32][33] The data of the selected samples were classified and analyzed by considering IA rupture as an independent factor and identified 10 hub genes that form part of early processes that lead to IA rupture. Moreover, association of immune cell infiltration with IA rupture was established in the current study where several immune-related signaling pathways involved in IA rupture were revealed.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from numerous studies shows that immune cells participate in initiation of IA by triggering production of molecules that initiate inflammation, as well as factors that induce pathological remodeling of vasculature. [30][31][32][33] The data of the selected samples were classified and analyzed by considering IA rupture as an independent factor and identified 10 hub genes that form part of early processes that lead to IA rupture. Moreover, association of immune cell infiltration with IA rupture was established in the current study where several immune-related signaling pathways involved in IA rupture were revealed.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that there is a large amount of inflammatory cell infiltration in IA tissues, and the levels of inflammatory cytokines in the cerebrospinal fluid of SAH are significantly increased, but there is no infiltration of inflammatory cells in the normal arterial wall [ 8 – 11 ]. The mechanism of inflammation involved in IA may be related to the inflammation-induced vascular endothelial damage, the degenerative vascular wall remodeling, and a high blood flow, including increased vascular wall shear stress [ 12 , 13 ]. Candidate gene association studies revealed that polymorphisms in interleukin 1 ( IL1 ), interleukin 6 ( IL6 ), interleukin 12 ( IL12 ), and tumor necrosis factor- α ( TNF-α ) genes are associated with IA in several populations [ 14 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Till now, the etiology of IA remains to be clarified; the genetic aspect, living habit, environment, and estrogen hormone are all reported to be closely related to IA development [3][4][5]. Among the potential risk factors of IA, abnormal hemodynamics is one of the location-specific dangerous factors, which show high relevance with vessel inflammation and atherosclerotic plaque [6].…”
mentioning
confidence: 99%